The international zero-leverage phenomenon - Bessler, Wolfgang; Drobetz, Wolfgang; Haller, Rebekka; Meier, Iwan (Journal of Corporate Finance, 2013)
We analyze the zero-leverage phenomenon around the world. Countries with a common law system, high creditor protection, and a dividend imputation or dividend relief tax system exhibit the highest percentage of zero-leverage firms. The increasing prevalence of zero-leverage firms in all sample countries is related to market-wide forces during our sample period, such as IPO waves, shifts in industry composition, increasing asset volatility, and decreasing corporate tax rates. Firm-level comparisons reveal that only a small number of firms deliberately maintain zero-leverage. Most zero-leverage firms are constrained by their debt capacity. Analyzing the time-series dynamics of leverage and investment behavior, we further show that firms which pursue a zero-leverage policy only for a short period of time seek financial flexibility.